2019
DOI: 10.2134/agronj2019.03.0191
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Yield Stability of Ley Farming System in Northern Quebec

Abstract: Predicted climate change is a threat to dairy farming operations in northern Quebec. Soil conservation measures and the timeframe of crop management may contribute to reducing yield variability and also support dairy herd populations. Our objective was to compare annual and cyclic barley (Hordeum vulgare L.) and forage yield stability for 3‐yr ley farming system (barley‐mixed, forage‐mixed, forage) over 24 yr of experimentation under contrasting soil conservation practices. Treatments were chisel or moldboard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The N-based application of animal manures has led to the excessive soil accumulation of P, Cu, and Zn [21,28] and has contributed to the eutrophication of surface waters [29]. Long-term experiments can assess a system's sustainability by monitoring the effects of fertilizer treatments on yield stability, nutrient management, soil chemical quality [30][31][32][33], and long-lasting carryover effects [34].…”
Section: Introductionmentioning
confidence: 99%
“…The N-based application of animal manures has led to the excessive soil accumulation of P, Cu, and Zn [21,28] and has contributed to the eutrophication of surface waters [29]. Long-term experiments can assess a system's sustainability by monitoring the effects of fertilizer treatments on yield stability, nutrient management, soil chemical quality [30][31][32][33], and long-lasting carryover effects [34].…”
Section: Introductionmentioning
confidence: 99%
“…In Quebec, Giroux and Lemieux (2000) suggested that fertilizer K management should not only consider crop response to K fertilization, but also soil K buildup and maintenance assisted by K budget and soil test K, cationic balance with Ca and Mg, and the balance between N and K fertilization. While MIN led to a negative K budget without any forage yield loss during 27 yr of experimentation at the same site (Damar et al., 2019), adding fertilizer K in soils with high illite‐like minerals have not necessarily an effect on forage yields (Ziadi, Simard, Tran, & Allard, 2001). It was also reported elsewhere that small or no K fertilizer application could maintain an adequate yield level of grass–clover leys over 40‐yr period of experiment in clayey soil (Andersson et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…72 • 33′ W) and ended in 2016 (after 27 yr). After discarding the 1989-1992 period following initiation (Damar et al, 2019), the monitoring period extended from 1993 to 2016. The climate is frigid continental.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation